Diversity of Fsih On Siak River Tebing Tinggi Okura Village Rumbai Timur District Pekanbaru Riau Province - Muhammad Irpan Syahputra; Muhammad Fauzi; Eni Sumarsih (Berkala Perikanan Terubuk, 2022)
Decreased water quality greatly affects the life of various aquatic organisms, one of which is fish. Various community activities around the watershed can produce a variety of contaminants, both organic and inorganic. These pollutants can contaminate the river either directly or indirectly. The polluted aquatic environment will affect the diversity of fish. The purpose of this study is to examine the diversity of fish in the Siak River of Tebing Tinggi Okura Village of Pekanbaru City which was conducted from June to July 2021. Survey method is used in this study. Fish sampling is done through fishing with local fishermen using fishing gear, namely “belat”. The results of the study showed the number of fish obtained in this study is as many as 7 fish families consisting of 13 species. The value of the diversity index (H') is 2.13, the dominance index (C) is 0.35 and the uniformity index (E) is 0.6. This results that the diversity of fish in the Siak River of Tebing Tinggi Okura Village is still relatively moderate. Low dominance index (C) value caused by thebalance of uniformity index value (E)